Identification of novel Fgf enhancers and their role in dental evolution. Issue 1 (18th June 2015) - Tapaltsyan, Vagan; Charles, Cyril; Hu, Jianxin; Mindell, David; Ahituv, Nadav; Wilson, Gregory M.; Black, Brian L.; Viriot, Laurent; Klein, Ophir D.
SUMMARY: Mammalian dental morphology is under strong evolutionary pressure because of its importance for mastication and diet. While the mechanisms underlying tooth development have been widely studied in model organisms, the role of genetic regulatory elements in patterning the different elements of the occlusal surface and crown height across species is not well understood. Previous studies showed that Fibroblast Growth Factor (FGF) genes are important regulators of tooth development that influence morphological variation. We hypothesized that inter‐specific variation in rodent dental morphology could be governed by nucleotide variation in genetic regulatory elements that modulate the spatial and temporal expression of the genes encoding FGF signaling molecules. In this study, we compared the variation in dental morphology across nine taxa of rodents to the variation in sequences of non‐coding evolutionary conserved regions (ECRs) of Fgf3, 4, 8, 9, and 10 . We correlated the variation in molar tooth cusp shape and the evolution of high molar crowns (hypsodonty) to the patterns of sequence variation in two ECRs, Fgf10ECR3, and Fgf9ECR1, respectively. By conducting luciferase and electrophoretic mobility shift assays, we determined that these ECRs could function as enhancers. These data suggest that emergence of hypsodonty and occlusal cusp patterning may have happened through the evolutionary changes in enhancers, such as Fgf9ECR1 and Fgf10ECR3, which affected the expression of major signaling molecules involved in tooth development.